1992
DOI: 10.1115/1.2920946
|View full text |Cite
|
Sign up to set email alerts
|

Slipper Balance in Axial Piston Pumps and Motors

Abstract: The paper presents the results of an experimental and theoretical investigation of the effect of clamping ratio and orifice size on the performance of slippers in axial piston pumps and motors. Polishing of the running face to a slightly convex form appears to be essential for successful operation under all conditions. It is shown that slippers operate perfectly satisfactorily with the orifice blanked and, indeed, are generally most stable in this condition. Introduction of the orifice in under-clamped slipper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The effects of slipper spin, tangential velocity, tilt, slipper non flatness, inlet orifice, and conditions for metal to metal contact, amongst others, have been investigated. The performance of composite slippers working with water based fluids has been studied by Li and Hooke [15] and the torque created on the spherical piston slipper interface and its effect onto the slipper dynamic performance has also been considered [1,2,16]. Slipper dynamic performance over one complete revolution was investigated by [17,18] finding a large variation in slipper central clearance and tilt depending on piston connection with tank or outlet ports.…”
mentioning
confidence: 99%
“…The effects of slipper spin, tangential velocity, tilt, slipper non flatness, inlet orifice, and conditions for metal to metal contact, amongst others, have been investigated. The performance of composite slippers working with water based fluids has been studied by Li and Hooke [15] and the torque created on the spherical piston slipper interface and its effect onto the slipper dynamic performance has also been considered [1,2,16]. Slipper dynamic performance over one complete revolution was investigated by [17,18] finding a large variation in slipper central clearance and tilt depending on piston connection with tank or outlet ports.…”
mentioning
confidence: 99%
“…[−3µωαr m1 sin θ r 2 + k 1 ]dθ [11] r m1 = r 1 + r 0 2 [12] First land: r 1 < r < r 2 p 2 = −3µωαr m2 sin θ r 2 2(h 02 + αr m2 cos θ ) 3 + k 3 (h 02 + αr m2 cos θ ) 3 ln(r) + k 4 [13] …”
Section: Flow and Pressure Distribution On Multiple Land Slippers Mamentioning
confidence: 99%
“…They investigated the oil film pressure distribution and load characteristics by considering the pressure-viscosity effect of the lubricant, the pressure-elasticity effect of the lubricating surface, and the properties of dynamic stiffness in the oil film. G. Rizzo et al Koc et al (1992) and Hooke (1989) carried out an experimental and theoretical investigation of the effects of deformation in slipper pad, clamping ratio, and orifice size on the load-carrying capacity of hydrostatic thrust bearing under a low-speed condition in axial piston pumps and motors. They concluded that polishing of the running face to a slightly convex form appeared to be essential for successful operation under all conditions; the orifice in under-clamped slippers could increase the clearance and destabilize the slipper, which would result in the slipper becoming sensitive to the effect of tilting couples; the design for over-clamped slippers seemed to depend on the precise value of the clamping ratio and the width of the slipper land.…”
Section: Introductionmentioning
confidence: 99%